KLASIFIKASI CITRA BATIK INDONESIA DAN MALAYSIA DENGAN METODE MODIFIED DISCRIMINANT ANALYSIS - Cynthia, Cynthia; Hendryli, Janson; Herwindiati, Dyah Erny (Computatio : Journal of Computer Science and Information Systems, 2019)
The application of Indonesian and Malaysian batik image classification using the Linear Discriminant Analysis (LDA) and Modified Discriminant Analysis (MDA) method is an introduction application that is used to classify images in the form of batik. Making this application uses the Java programming language to run feature retrieval methods, namely Color Histogram and Daubechies Wavelet and classification methods, namely LDA and MDA. Testing is done by blackbox testing method and confusion matrix. Tests are performed using color features, texture features, and a combination of training images and new test images. The best percentage test results are testing using color features, whereas with texture and the combination of both features get a slightly lower test percentage result.Aplikasi klasifikasi citra batik Indonesia dan Malaysia dengan metode Linear Discriminant Analysis (LDA) dan Modified Discriminant Analysis (MDA) merupakan aplikasi pengenalan yang digunakan untuk mengklasifikasi citra berupa batik. Pembuatan aplikasi ini menggunakan bahasa pemrograman Java untuk menjalankan metode pengambilan fitur yaitu Color Histogram dan Daubechies Wavelet dan metode pengklasifikasian yaitu LDA dan MDA. Pengujian dilakukan dengan metode blackbox testing dan matriks konfusi. Pengujian dilakukan dengan menggunakan fitur ciri warna, ciri tekstur, dan gabungan dari citra latih dan citra uji baru. Hasil persentase pengujian terbaik adalah pengujian dengan menggunakan ciri warna, sedangkan dengan ciri tekstur dan gabungan mendapatkan hasil persentase pengujian sedikit rendah.